2019
DOI: 10.1186/s13072-019-0313-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility and transcription dynamics during in vitro astrocyte differentiation of Huntington’s Disease Monkey pluripotent stem cells

Abstract: BackgroundHuntington’s Disease (HD) is a fatal neurodegenerative disorder caused by a CAG repeat expansion, resulting in a mutant huntingtin protein. While it is now clear that astrocytes are affected by HD and significantly contribute to neuronal dysfunction and pathogenesis, the alterations in the transcriptional and epigenetic profiles in HD astrocytes have yet to be characterized. Here, we examine global transcription and chromatin accessibility dynamics during in vitro astrocyte differentiation in a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 148 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…However, these models may be altered by the type of mutations as well as by the frequency of the suggested modifiers in the populations, and this might explain the effect of ethnicity and might also indicate an indirect effect of the environment over genetics (Kousi and Katsanis, 2015;Bis-Brewer and Züchner, 2018;Amin et al, 2021). Numerous studies have also suggested an impact of epigenetics in Parkinson's, Alzheimer's, Huntington's diseases, cerebellar ataxias (CA), and ALS (Chestnut et al, 2011;Desplats et al, 2011;Chouliaras et al, 2013;Goodnight et al, 2019;Haertle et al, 2019;Jia et al, 2019;Lardenoije et al, 2019). A role for epigenetics in apoptosis was suggested in motor neuron pathology in ALS, with the upregulation of DNA methylase increasing DNA methylation which results in apoptosis (Chestnut et al, 2011).…”
Section: Genetic Diagnosis: Approaches Yield and Gap In Genetic Etiologymentioning
confidence: 99%
“…However, these models may be altered by the type of mutations as well as by the frequency of the suggested modifiers in the populations, and this might explain the effect of ethnicity and might also indicate an indirect effect of the environment over genetics (Kousi and Katsanis, 2015;Bis-Brewer and Züchner, 2018;Amin et al, 2021). Numerous studies have also suggested an impact of epigenetics in Parkinson's, Alzheimer's, Huntington's diseases, cerebellar ataxias (CA), and ALS (Chestnut et al, 2011;Desplats et al, 2011;Chouliaras et al, 2013;Goodnight et al, 2019;Haertle et al, 2019;Jia et al, 2019;Lardenoije et al, 2019). A role for epigenetics in apoptosis was suggested in motor neuron pathology in ALS, with the upregulation of DNA methylase increasing DNA methylation which results in apoptosis (Chestnut et al, 2011).…”
Section: Genetic Diagnosis: Approaches Yield and Gap In Genetic Etiologymentioning
confidence: 99%
“…In addition, E2F1 regulates cell cycle gene transcription in a H2AZ- and BET bromodomain protein-dependent manner in melanoma and GBM [ 14 , 17 , 28 ]. There also appears to be a connection between chromatin accessibility at E2F target genes and cell identity as it decreases when wing and pluripotent stem cells differentiate and exit from cell cycle [ 29 , 30 ]. Collectively, these observations raise the possibility that E2Fs may regulate H2AZ gene transcription, which in turn affect cell proliferation and stemness of GSC.…”
Section: Introductionmentioning
confidence: 99%
“…For this, we retrieved 14 studies and 79 datasets (Table 5; Supplementary Figure S1). Among 14 studies, 12 were related to mouse models (Ng et al, 2013;Vashishtha et al, 2013;Crotti et al, 2014;Mielcarek et al, 2014;Achour et al, 2015;Langfelder et al, 2016;Miller et al, 2016;Handley et al, 2017;Jacobsen et al, 2017;Pan et al, 2018;Goodnight et al, 2019;Radulescu et al, 2019;Yildirim et al, 2019;Lee et al, 2020;Wertz et al, 2020), one study was related to sheep (Handley et al, 2017) and one to monkey (Goodnight et al, 2019).…”
Section: Transcriptional Changes In Non-human Modelsmentioning
confidence: 99%
“…In early stage, genes such as Clspn, Gpr153, Gpx6, Krt9, Penk and Plk5 were frequently dysregulated, while in intermediate stage, Penk, Atp2b1, Scn4b, TABLE 5 | Characteristics of included non human HD studies. The table summarizes the PMID, sample, cell type, reference and key findings of each included non human study (Ng et al, 2013;Vashishtha et al, 2013;Crotti et al, 2014;Mielcarek et al, 2014;Langfelder et al, 2016;Handley et al, 2017;Jacobsen et al, 2017;Pan et al, 2018;Goodnight et al, 2019;Radulescu et al, 2019;Yildirim et al, 2019;Lee et al, 2020;Wertz et al, 2020). Pde10a and Rbfox1 were dysregulated to name a few.…”
Section: Transcriptional Changes In Non-human Modelsmentioning
confidence: 99%